2011
DOI: 10.1111/j.1600-0501.2011.02206.x
|View full text |Cite
|
Sign up to set email alerts
|

Failure analysis of fractured dental zirconia implants

Abstract: The present study identified a fracture rate of nearly 10% within a follow-up period of 36.75 months after prosthetic loading. Ninety-two per cent of the fractured implants were so-called diameter reduced implants (diameter 3.25 mm). These diameter reduced implants cannot be recommended for further clinical use. Improvement of the ceramic material and modification of the implant geometry has to be carried out to reduce the failure rate of small-sized ceramic implants. Nevertheless, due to the lack of appropria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 21 publications
1
75
0
8
Order By: Relevance
“…The clinical study by Dahlert et al agreed with this finding [43]. They reported that the fracture rate of one-piece zirconia implants was nearly 10%, where 13 of 170 inserted implants fractured with an average in situ period of 36.75 ± 5.34 months.…”
Section: Implant Loss and Fracturesupporting
confidence: 77%
See 1 more Smart Citation
“…The clinical study by Dahlert et al agreed with this finding [43]. They reported that the fracture rate of one-piece zirconia implants was nearly 10%, where 13 of 170 inserted implants fractured with an average in situ period of 36.75 ± 5.34 months.…”
Section: Implant Loss and Fracturesupporting
confidence: 77%
“…Zirconia is strong under compressive stress, but it is sensitive to shear and tensile stresses. The greater the angle between the biting force direction and the implant axis, the greater the shear stresses and an enhanced risk of zirconia implant fracture [41][42][43].…”
Section: Implant Loss and Fracturementioning
confidence: 99%
“…Therefore, fracture can be a problem. Gahlert et al analyzed fractured zirconia dental implants and found that approximately 10% of the implants were fractured 36.75 months after prosthetic loading 33) . The causes of fracture were the use of implant bodies with a small diameter and occlusal overloading.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study although intraoral grinding was performed for case 1 and 2, any implant fracture was not observed during approximately 6 year follow-up. 27 One-piece implants generally require soft tissue formation after insertion due to their submucosally submerged prosthetic platform. An immediate provisionalization is recommended for one-piece zirconia implants.…”
Section: Figurementioning
confidence: 99%